Slip sheet for glass plate

KR103021649B1Active Publication Date: 2026-09-18AGC INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020210114768
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-26
Filing Date
2021-08-30
Publication Date
2026-09-18
Estimated Expiration
2041-08-30

Smart Images

  • Figure 112021100039178-PAT00004_ABST
    Figure 112021100039178-PAT00004_ABST
Patent Text Reader

Abstract

The purpose is to provide a laminate for glass plates that suppresses the adhesion of silicon-containing foreign substances, particularly micro-sized silica foreign substances, to the surface of the glass plate. The laminate for glass plates is composed mainly of cellulose pulp, and when the silicon concentration measured by fluorescent X-ray analysis is X and the calcium concentration is Y, X is 200 ppm or less, and the X / Y ratio, which is the value obtained by dividing the silicon concentration by the calcium concentration, is 4.00 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a laminate for glass plates, a glass plate laminate, and a glass plate bale. Background Technology

[0002] In glass plates used in flat panel displays (FPDs), such as liquid crystal displays, fine electronic wiring (hereinafter also referred to as "wiring") is formed on the surface of the glass plate, so slight scratches or contamination on the surface can cause defects such as short circuits. Therefore, a high degree of cleanliness is required on the surface of the glass plate.

[0003] Glass plates are transported in stacked layers for the purpose of increasing transport efficiency. At this time, a laminate for glass plates (hereinafter also simply referred to as "laminate") is interposed between adjacent glass plates to prevent scratches or the like from forming on the surface of the glass plates during transport.

[0004] However, foreign substances introduced during the lamination manufacturing process or the influence of various chemicals may cause foreign matter to adhere to the surface of the glass plate from the laminate. Although most of the foreign matter attached to the glass plate surface is removed by cleaning prior to the process of forming wiring on the glass plate surface, some remains on the surface even after cleaning, posing a risk of causing wire breakage. Therefore, there is a need for a laminate for glass plates that reduces the adhesion of foreign matter to the surface of the glass plate.

[0005] In Patent Document 1, the surface contamination of a glass plate is reduced by lowering the concentration of aluminum, silicon, magnesium, etc., included in the laminate for the glass plate. Prior art literature

[0006] Japanese Patent Publication No. 2017-210286 The problem to be solved

[0007] However, with the recent increase in the precision of displays, the width and pitch of the wiring formed on the surface of the glass plate have become finer than before, and even when using a laminate for glass plates such as Patent Document 1, problems such as wire breakage have occurred during wiring formation.

[0008] Upon investigating the aforementioned problem, the inventors discovered that the cause was microscopic silica foreign matter remaining on the surface of the glass plate even after cleaning. Since microscopic silica foreign matter is difficult to remove during the cleaning process prior to forming the wiring, it is important to prevent such foreign matter from adhering to the surface of the glass plate.

[0009] The present invention aims to provide a laminate for glass plates that suppresses the occurrence of defects, such as wire breakage, during wiring formation by suppressing the attachment of micro-sized silica foreign matter to the surface of the glass plate. means of solving the problem

[0010] The laminate for glass plates according to the present invention is characterized by having cellulose pulp as the main component, a basis weight of 10 g / m² or more and 100 g / m² or less, and the laminate for glass plates is characterized by having X as the silicon concentration measured by fluorescent X-ray analysis and Y as the calcium concentration, wherein X is 200 ppm or less and the X / Y ratio, which is the value obtained by dividing the silicon concentration by the calcium concentration, is 4.00 or less.

[0011] For the above-mentioned laminate for glass plates, it is preferable that the X / Z ratio, which is the value obtained by dividing the silicon concentration by the magnesium concentration when the magnesium concentration measured by fluorescent X-ray analysis is Z, is 3.00 or less.

[0012] It is preferable that the above Z be 20 ppm or more and 100 ppm or less.

[0013] It is preferable that the above Y be 20 ppm or more and 400 ppm or less.

[0014] It is preferable that the number of silicon-containing foreign substances, ranging from 0.5㎛ to 50㎛, present on at least one laminated surface of the above glass plate is 2000 pieces / mm² or less.

[0015] It is preferable that the number of silicon-containing foreign substances of 1㎛ or more and 10㎛ or less present on at least one laminated surface of the above glass plate is 1000 pieces / mm² or less.

[0016] It is preferable that the above laminate for glass plates has a number of silica foreign substances of 0.5㎛ or more and 50㎛ or less present on at least one laminate surface of 100 pieces / mm² or less.

[0017] It is preferable that the above laminate for glass plates has a number of silica foreign substances of 1 μm or more and 10 μm or less present on at least one laminate surface of 50 particles / mm² or less.

[0018] It is preferable that the air permeability resistance of the laminate for the glass plate above be 5 seconds or more.

[0019] The glass plate laminate according to the present invention laminates at least two glass plates and has a laminate for glass plates according to the present invention between adjacent glass plates.

[0020] The glass plate bale according to the present invention has the glass plate laminate and a pallet for loading the glass plate laminate. Effects of the invention

[0021] A laminate for glass plates can be provided that suppresses the adhesion of micro-sized silica foreign matter to the surface of the glass plate. By doing so, the occurrence of defects such as open circuits during wiring formation can be suppressed. Brief explanation of the drawing

[0022] Figure 1 is a conceptual diagram illustrating a method for manufacturing a laminate for glass plates. Figure 2 is a conceptual diagram illustrating a pallet for loading glass plates. FIG. 3 is a conceptual diagram illustrating one embodiment of a glass plate bale. Specific details for implementing the invention

[0023] Hereinafter, preferred embodiments of a laminate for a glass plate according to the present invention will be described. The embodiments described below are examples, and the present invention is not to be interpreted as being limited to these embodiments.

[0024] For the sake of transport efficiency, at least two glass plates are laminated and loaded onto a pallet for transport. A laminate formed by laminating at least two glass plates and interposing a laminate between adjacent glass plates is called a glass plate laminate, and a glass plate laminate loaded onto a pallet is called a glass plate bundle. In a glass plate laminate, if the glass plates come into contact with each other, there is a risk of scratches occurring on the surface of the glass plates. It is known that such scratches cause problems such as wire breakage in manufacturing processes for displays, etc. Therefore, by interposing a glass plate laminate between the glass plates, scratches on the surface of the glass plates are suppressed.

[0025] However, foreign substances contained in the laminate for glass plates may adhere to the surface of the glass plate, causing problems such as wire breakage. In particular, with the recent increase in the precision of displays, issues such as wire breakage have begun to occur even when using laminates for glass plates that were not previously problematic.

[0026] Therefore, the inventors analyzed the foreign matter attached to the glass plate. As a result, it was found that a large amount of silicon-containing foreign matter was attached to the surface of the glass plate. Furthermore, among the silicon-containing foreign matter, it was discovered that micro-sized silica foreign matter is particularly difficult to remove by cleaning before forming the wiring, and remains even after cleaning, causing problems. In this specification, micro-sized silica foreign matter refers to silica foreign matter with a longest diameter of 10 μm or less.

[0027] In addition, silica foreign matter with a longest diameter of more than 10㎛ is easy to remove by cleaning performed before forming wiring on the glass plate, so it is considered less likely to cause defects such as wire breakage compared to silica foreign matter with a longest diameter of 10㎛ or less.

[0028] Among silicon-containing foreign substances, micro-sized silica foreign substances are particularly difficult to remove by cleaning and tend to remain even after cleaning. This is thought to be because, unlike silicon-containing foreign substances other than silica foreign substances such as talc, which are often spherical, silica foreign substances are often flat in shape. In other words, since flat shapes have a low height, they are difficult to remove by cleaning processes such as brush cleaning, and thus tend to remain.

[0029] Furthermore, the inventors discovered that the silica foreign matter remaining on the surface of the glass plate was attached to the surface of the glass plate from the laminate. From the above, it is important to reduce the micro-sized silica foreign matter present in the laminate for the glass plate.

[0030] (Method for manufacturing laminated paper for glass plates)

[0031] The raw material liquid for the glass plate lamination (liquid obtained by diluting pulp with water) is supplied in a sheet shape from the head box (112) onto the lower wire (116) installed in the wire part (114). The raw material liquid supplied to the lower wire (116) is then inserted by the lower wire (116) and the upper wire (118), thereby expanding to a uniform thickness and also being dehydrated to become wet paper.

[0032] The lower wire (116) and upper wire (118) of the wire part (114) are permeable membranes formed in the shape of a strip. Specifically, they are a mesh made of plastic or metal material, or a strip made of felt containing natural or synthetic fibers.

[0033] The lower wire (116) and the upper wire (118) are connected to a plurality of rollers, and by transmitting the driving force of a motor (not shown) to the driving roller among the plurality of rollers, they are moved around at a predetermined speed.

[0034] The wet material formed by the wire part (114) is conveyed to a press part (120) having a press roller, a felt in the shape of a continuous strip, and a press roller stand, where further dehydration and pressing are performed.

[0035] The wet material that has passed through the press part (120) is returned to the dryer part (124) which consists of a plurality of rollers, and is dried in an atmosphere of, for example, about 120°C while passing through the dryer part (124).

[0036] When passing through the dryer part (124), if the wet material is conveyed at high speed as is, there is a risk of the paper being cut, so an auxiliary material called a canvas is conveyed in contact with the wet material.

[0037] The paper dried in the dryer part (124) is returned to the calendar part (126), and the paper may be calendered by means of a calender roll support return, etc., to smooth the front and back surfaces. Additionally, if necessary, a coater part may be provided between the dryer part (124) and the calendar part (126), and paint or the like may be applied to the surface of the smoothed paper.

[0038] The paper that has undergone calendar processing in the calendar part (126) is wound onto a reel (128) as a laminate for glass plates and becomes a roll shape (hereinafter referred to as a jumbo roll (130)).

[0039] The laminate for glass plates made of a jumbo roll (130) is typically, for example, cut to a width according to the product and wound, and becomes a laminate roll (42) that is wound with a long laminate for glass plates of a predetermined length of about 8,000 to 10,000 m.

[0040] The laminate for glass plates is fed from a jumbo roll (130), cut to a predetermined width (cut in the length direction) by a cutter (134), and wound by a winder (136). When the laminate for glass plates fed from the jumbo roll (130) reaches a predetermined length, it is cut to a predetermined length (cut in the width direction) by a cutter (134), and the laminate for glass plates is wound to a predetermined width to form a laminate roll (42).

[0041] The laminate for long glass plates wound on a lamination roll (42) is cut into a cut sheet shape (rectangular shape) of the size according to the glass plates to be laminated, and is interposed between the glass plates to be laminated.

[0042] (Silicon concentration)

[0043] Silicon contained in laminates for glass plates originates mainly from raw materials such as cellulose pulp, water, and dust from the air mixed in during the manufacturing process. In the manufactured laminates for glass plates, silicon exists mainly as silicon-containing foreign substances such as hydrated magnesium silicate (hereinafter also referred to as "talc") or silica.

[0044] The laminate for glass plates of the present invention has a silicon concentration of 200 ppm or less when measured by fluorescent X-ray analysis, thereby sufficiently reducing silica foreign matter in the laminate for glass plates and suppressing the occurrence of defects such as wire breakage.

[0045] The above silicon concentration is preferably 150 ppm or less, more preferably 130 ppm or less, even more preferably 100 ppm or less, and particularly preferably 50 ppm or less.

[0046] In addition, in this specification, the silicon concentration when a laminate for a glass plate is measured by fluorescent X-ray analysis is also referred to as X. X is measured by the following method.

[0047] (Method for measuring silicon concentration X)

[0048] Fluorescent X-ray analysis in the present invention can be performed using a commercially available fluorescent X-ray analysis device, such as ZXS PRIMUS (Rigaku Co., Ltd.). As a pretreatment for fluorescent X-ray analysis, the laminate for glass plates is cut in advance to a size suitable for measurement using a blade or the like. The cut paper is loaded onto a sample stand. At this time, to ensure that the components of the sample stand do not become noise during measurement, a sample stand with a high purity and a pre-established composition may be used, a cup-shaped sample stand with a deep bottom may be used, or laminates for glass plates may be stacked. Next, a cover with a hole in the measurement area is used to secure the laminate for glass plates. The sample stand is placed into the fluorescent X-ray analysis device, and after the inside of the device is evacuated, X-rays are irradiated onto the measurement surface, and the fluorescent X-rays generated from the laminate for glass plates are measured and analyzed.

[0049] Since a wider evaluation area yields more stable results, the evaluation area is preferably 10 square millimeters or more, more preferably 100 square millimeters or more, and even more preferably 600 square millimeters or more. Unless otherwise specifically stated in this specification, the evaluation area is 700 square millimeters.

[0050] For the quantification of the detected elements, a reference sample with a known concentration was measured in advance, and the values ​​of each element were corrected from the X-ray intensity. The power during measurement was set to 3000W.

[0051] During measurement, the content of each element, including sodium, magnesium, aluminum, silicon, phosphorus, sulfur, chlorine, potassium, calcium, iron, nickel, copper, and zircon, was quantified.

[0052] If the silicon concentration is too low, the foaming properties of the raw material solution for glass board lamination are poor when stirred, and holes may be formed in the glass board lamination. For this reason, the silicon concentration is preferably 10 ppm or higher, more preferably 15 ppm or higher, and even more preferably 20 ppm or higher.

[0053] Silicon concentration is affected by the cellulose pulp of the raw material, the water of the raw material, and the manufacturing method of the laminate.

[0054] Silicon concentration can be reduced by selecting cellulose pulp as a raw material that does not contain silicone oil or contains a small amount of it, does not contain talc as a pitch control agent, or has fine ore and dust removed by applying strong centrifugal force. Silicon concentration can also be reduced by using water as a raw material from which silicon components derived from ore in groundwater or river water have been removed through sufficient filtration. Furthermore, in the method of manufacturing laminated paper, silicon concentration can be reduced by preventing the intrusion of dust by performing the paper-making process in a clean room, or by separating the paper-making process using cellulose pulp containing silicone oil from the paper-making process for laminated paper for glass plates.

[0055] As the above cellulose pulp, a laminate for glass plates containing various raw materials such as chemical pulp (KP), sulfite pulp (SP), soda pulp (AP); semi-chemical pulp (SCP), chemical ground wood pulp (CGP); mechanical pulp (GP), thermomechanical pulp (TMP, BCTMP), refiner ground wood pulp (RGP); non-wood fiber pulp made from paper mulberry, three-branched paper mulberry, hemp, kenaf, etc.; synthetic pulp; etc. may be used. In addition, a mixture of these may also be used.

[0056] (Calcium concentration)

[0057] Calcium contained in laminates for glass plates originates mainly from raw materials such as cellulose pulp or water, or from dust in the air mixed in during the manufacturing process. In the manufactured laminates for glass plates, calcium exists as silicon-containing foreign substances, such as calcium metasilicate and calcium orthosilicate, or as calcium carbonate.

[0058] In this specification, the calcium concentration when a laminate for a glass plate is measured by fluorescent X-ray analysis is also referred to as Y. Y is measured by the same procedure as the above (method for measuring silicon concentration X).

[0059] The smaller the X / Y ratio, which is the value obtained by dividing the silicon concentration by the calcium concentration, the more calcium is present relative to silicon. Since calcium exists not only as calcium carbonate but also as silicon-containing compounds such as calcium metasilicate and calcium orthosilicate, it is thought that the larger the calcium concentration Y, the smaller the proportion of silicon existing as silica, and thus the less silica impurity there is.

[0060] The laminate for glass plates according to the present invention was able to sufficiently reduce silica foreign matter in the laminate for glass plates by setting the X / Y ratio to 4.00 or less. The X / Y ratio is preferably 3.50 or less, more preferably 3.00 or less, even more preferably 2.00 or less, particularly preferably 1.00 or less, and most preferably 0.50 or less.

[0061] In addition, if Y is too large, it is thought that silica impurities will decrease, but calcium-containing impurities such as calcium carbonate will increase, which may cause problems. Therefore, Y is preferably 400 ppm or less, more preferably 300 ppm or less, and even more preferably 250 ppm or less.

[0062] In addition, if Y is too small, the foaming properties of the raw material liquid for glass plates are poor when stirred, and holes may be formed in the glass plate laminate. For this reason, Y is preferably 20 ppm or more, more preferably 30 ppm or more, and even more preferably 50 ppm or more.

[0063] By using virgin pulp with a high calcium content, the X / Y ratio can be reduced.

[0064] (Magnesium concentration)

[0065] Magnesium contained in laminates for glass plates originates mainly from raw materials such as cellulose pulp, water, and airborne dust mixed in during the manufacturing process. In the manufactured laminates for glass plates, magnesium exists mainly as silicon-containing foreign matter such as talc.

[0066] In this specification, the magnesium concentration when a laminate for a glass plate is measured by fluorescent X-ray analysis is also referred to as Z. Z is measured by the same procedure as the above (method for measuring silicon concentration X).

[0067] The smaller the X / Z ratio, which is the value obtained by dividing the silicon concentration by the magnesium concentration, the more magnesium is present relative to silicon. As mentioned above, since magnesium exists as a silicon-containing compound such as talc, it is thought that the larger Z is, the smaller the proportion of silicon existing as silica becomes, and thus the less silica impurity is reduced.

[0068] The X / Z ratio of the laminate for glass plates of the present invention is preferably 3.00 or less, more preferably 2.50 or less, even more preferably 2.00 or less, and particularly preferably 1.00 or less.

[0069] In addition, it is thought that if Z is large, silica impurities decrease, but talc increases, which may cause problems. Therefore, the magnesium content is preferably 100 ppm or less, and more preferably 70 ppm or less. The lower limit of Z is not particularly limited, but 10 ppm or more is preferred, and 20 ppm or more is more preferred.

[0070] (Method for measuring silicon-containing foreign matter and silica foreign matter)

[0071] Silicon-containing foreign matter is measured, for example, by a scanning electron microscope and an energy-dispersive X-ray analyzer installed on the scanning electron microscope. As a pretreatment for measurement, a conductive film treatment of an element not to be measured, such as carbon or platinum, may be performed on a small cut sample. After setting the laminate in the scanning electron microscope, a back-field electron detector is used to identify elements heavier than carbon, which is the element mainly constituting the laminate, from the brightness of the image. In this method using a back-field electron detector, elements heavier than carbon are generally represented by bright pixels. Initially, 100 areas of, for example, 0.1 mm × 0.1 mm are measured. Next, when measuring the number of silicon-containing foreign matter and silica foreign matter ranging from 1 μm to 10 μm, foreign matter other than carbon, 1 μm or larger, is counted. For each foreign substance detected by this reflection electron detector, the size was calculated from the number of pixels, and for each particle with a longest diameter of 1 μm or more and 10 μm or less, the elements were analyzed one by one using an energy-dispersive X-ray analyzer. Among the elements excluding carbon and oxygen, particles containing 10 weight% or more of silicon were designated as silicon-containing substances. Additionally, particles containing 80 weight% or more of silicon were designated as silica foreign substances.

[0072] When measuring the number of silicon-containing foreign substances and silica foreign substances of 0.5㎛ or more and 50㎛ or less, foreign substances other than carbon of 0.5㎛ or more were counted and measured in the same way.

[0073] When the longest diameter of silicon-containing foreign matter is less than 1 μm and is sufficiently smaller than the wiring width or pitch width, it is unlikely to cause problems such as wire breakage. In addition, it was found that among silica foreign matter, the smaller the longest diameter, the more difficult it is to remove by cleaning, and in particular, silica foreign matter with a longest diameter of 10 μm or less tends to remain on the surface of the glass plate even after cleaning.

[0074] In the laminate of the present embodiment, it is preferable that the silicon-containing foreign matter of 0.5㎛ to 50㎛ present on at least one surface of the laminate be 2000 pieces / mm² or less, more preferable that it be 1000 pieces / mm² or less, even more preferable that it be 200 pieces / mm² or less, and particularly preferable that it be 20 pieces / mm² or less. It is believed that the less silicon-containing foreign matter of 0.5㎛ to 50㎛ contained in the laminate, the less problematic silica foreign matter of 1㎛ to 10㎛ is also found.

[0075] In addition, in the laminate of the present embodiment, it is preferable that the silicon-containing foreign matter of 1 μm or more and 10 μm or less present on at least one surface of the laminate be 1,000 pieces / mm² or less, more preferable that it be 100 pieces / mm² or less, and even more preferable that it be 10 pieces / mm² or less. It is believed that the less silicon-containing foreign matter of 1 μm or more and 10 μm or less contained in the laminate, the less silica foreign matter of 1 μm or more and 10 μm or less is also present.

[0076] In addition, in the laminate of the present embodiment, silica foreign matter of 0.5㎛ to 50㎛ present on at least one surface of the laminate is preferably 100 pieces / mm² or less, more preferably 50 pieces / mm² or less, even more preferably 20 pieces / mm² or less, and particularly preferably 10 pieces / mm² or less. It is believed that the less silica foreign matter of 0.5㎛ to 50㎛ contained in the laminate, the less silica foreign matter of 1㎛ to 10㎛ is also present.

[0077] In addition, in the laminate of the present embodiment, silica foreign matter of 1 μm or more and 10 μm or less present on at least one laminate surface is preferably 50 pieces / mm² or less, more preferably 30 pieces / mm² or less, even more preferably 10 pieces / mm² or less, and particularly preferably 5 pieces / mm² or less. The less silica foreign matter of 1 μm or more and 10 μm or less is present, the less of the silica foreign matter is transferred to the glass plate, making it less likely for problems such as wire breakage to occur.

[0078] (Speculation resistance)

[0079] The air permeability resistance is measured by a method in accordance with JIS P8117. The air permeability resistance is preferably 5 seconds or more, more preferably 10 seconds or more, and particularly preferably 15 seconds or more. If the air permeability resistance is 5 seconds or more, it is easy to remove only one sheet of laminated paper from the glass plate bale using a vacuum suction pad. On the other hand, if the air permeability resistance is less than 5 seconds, an abnormality is likely to occur in which the glass plate beneath the laminated paper to be removed is simultaneously removed when attempting to remove the laminated paper from the glass plate bale using a vacuum suction pad. Furthermore, while the upper limit of the air permeability resistance is not specifically limited, it is preferably 50 seconds or less, more preferably 45 seconds or less, and even more preferably 40 seconds or less.

[0080] (Characteristics of laminated paper for glass plates)

[0081] The basis weight of the laminate for glass plates is measured by a method in accordance with JIS P8118. A smaller basis weight of the laminate is desirable because it results in a smaller mass during transport, but if it is too small, sufficient cushioning cannot be obtained. Therefore, a basis weight of 10 g / m² or more is preferable, 20 g / m² or more is more preferable, and 30 g / m² or more is even more preferable. Furthermore, a basis weight of too large is undesirable because it results in a larger mass during transport. Therefore, a basis weight of 100 g / m² or less is preferable, 90 g / m² or less is more preferable, and 80 g / m² or less is even more preferable.

[0082] From the perspective of cushioning properties, the thickness of the laminate is preferably 50㎛ or more and 200㎛ or less. In addition, the density of the laminate is preferably 0.30g / cm³ or more and 1.00g / cm³ or less.

[0083] (Glass plate laminate)

[0084] The glass plate laminate (12) of the present embodiment has at least two glass plates (14) laminated together and has a glass plate laminate (16) according to the present invention between adjacent glass plates.

[0085] (Glass plate bale)

[0086] The glass plate bale (10) of the present embodiment has a glass plate laminate (12) and a pallet for loading the glass plate laminate (12).

[0087] The pallet is a known pallet for baling glass plates and has a base (22), an inclined plate (18) installed on the upper surface of the base (22), and a stacking plate (24) that supports the end surface of the glass plate stack (12). The angle θ of the stacking plate (24) and the inclined plate (18) is not particularly limited as long as it allows for stable stacking of the glass plates (14), but 90° is preferred.

[0088] The angle γ of the inclined platform (18) is the angle between the inclined platform (18) and the horizontal plane. That is, as shown in FIG. 1, when the upper surface of the platform where the inclined platform (18) and the loading platform (24) are installed is horizontal, the angle γ of the inclined platform (18) refers to the angle formed by the inclined platform (18) and the platform (22). If the angle γ of the inclined platform (18) is made closer to 90°, it leads to space saving, but since a large pressure is applied to the end surface of the glass plate (14), there is a risk of defects such as cutting. Also, if the inclined platform (18) is made closer to 0°, the pressure applied to the glass plate (14) is dispersed and defects such as cutting on the end surface can be suppressed, but since a large space is required, the efficiency of storage or transport decreases. In the present specification, a pallet with an angle of 10° or less of the inclined plate (18) is called a flat pallet, and a pallet with an angle greater than 10° is called a longitudinal pallet.

[0089] The pallet used may be a flat pallet or a vertical pallet, but in the case of a large glass plate, a large pressure is applied to the end of the glass plate (14) due to the self-weight of the glass plate (14). Therefore, in the case of a large glass plate, it is preferable to use a pallet that loads the glass plate in a flat state. Also, as the glass plate (14) becomes larger, the pressure applied to the end surface of the glass plate (14) increases, so the angle of the incline is preferably 0° or more and 5° or less, more preferably 0° or more and 3° or less, and even more preferably 0° or more and 1° or less. However, there are cases where the glass plate (14) cannot be stored in a flat pallet when transporting it in a truck or container. Therefore, a vertical pallet may be used to save space.

[0090] A large glass plate refers to, for example, a glass plate with at least one side of 2400 mm or more, and as a specific example, a glass plate with a long side of 2400 mm or more and a short side of 2000 mm or more. The above large glass plate is preferably a glass plate with at least one side of 2400 mm or more, for example, a glass plate with a long side of 2400 mm or more and a short side of 2100 mm or more; more preferably a glass plate with at least one side of 3000 mm or more, for example, a glass plate with a long side of 3000 mm or more and a short side of 2800 mm or more; even more preferably a glass plate with at least one side of 3200 mm or more, for example, a glass plate with a long side of 3200 mm or more and a short side of 2900 mm or more; and particularly preferably a glass plate with at least one side of 3300 mm or more, for example, a glass plate with a long side of 3300 mm or more and a short side of 2950 mm or more.

[0091] The thickness of the glass plate (14) is preferably 1 mm or less. By making the glass plate (14) thin, weight reduction can be achieved. The thickness of the glass plate (14) of the present invention is more preferably 0.75 mm or less, more preferably 0.6 mm or less, particularly preferably 0.5 mm or less, and most preferably 0.4 mm or less. The thickness may be 0.1 mm or less, or 0.05 mm or less. However, from the perspective of preventing bending due to self-weight, the thickness is preferably 0.1 mm or more, and more preferably 0.2 mm or more.

[0092] It is preferable to use the glass plate (14) for a display. Since there is less silica foreign matter of 1 μm or more and 10 μm or less present on the main surface of the glass plate (14), defects such as wire breakage can be suppressed. As a display, it is preferable to use it as a substrate for a liquid crystal display.

[0093] Although the glass plate laminate (16), glass plate laminate (12), and glass plate bale (10) have been described in detail above, the present invention is not limited to the examples described above, and it is understood that various improvements or modifications may be made within the scope of not deviating from the gist of the present invention.

[0094] <Example>

[0095] The present invention will be described in detail below by way of examples, but the present invention is not limited thereto. In the following, Examples 1 to 4 are examples, and Examples 5 to 7 are comparative examples. In addition, for cases not specifically described, the manufactured laminate was measured after treatment in accordance with JIS P8111.

[0096] The silicon, magnesium, and calcium concentrations contained in the laminates of Examples 1 to 7 were each measured twice using fluorescence X-ray analysis, and the average values ​​were calculated. Next, the number of silicon-containing foreign substances (number / mm²) with a longest diameter of 0.5㎛ or more and 50㎛ or less and 1㎛ or more and 10㎛ or less, and the number of silica foreign substances (number / mm²) with a longest diameter of 0.5㎛ or more and 50㎛ or less and 1㎛ or more and 10㎛ or less were measured using a scanning electron microscope and an energy-dispersive X-ray analysis device installed on the scanning electron microscope. Silicon-containing foreign substances and silica foreign substances of each size were each measured twice using different laminates, and the average values ​​were calculated.

[0097] The laminates for glass plates of Examples 1 to 7 were formed into a size of 2330 mm × 1990 mm, and each had a plate thickness of 0.5 mm and were interposed between glass plates for FPDs of a size of 2250 mm × 1950 mm to form a glass plate laminate in which multiple glass plates were laminated.

[0098] Each laminate of glass plates was loaded onto a vertical pallet as shown in Fig. 2 (600 glass plates), and a glass plate bale was produced. The produced glass plate bale was stored for 10 days.

[0099] From the glass plate bale, the glass plate closest to the inclined plate of the pallet was removed, and after cleaning the glass plate, the number of foreign substances remaining on the surface of the glass plate was measured using an optical inspection device.

[0100] Each measurement was performed using the following method.

[0101] Measurement of Elemental Concentration in Glass Plate Laminates by Fluorescent X-ray Analysis

[0102] The approximate center of the laminate was measured using a fluorescent X-ray analyzer (Manufacturer: Rigaku Co., Ltd., Model: ZXS PRIMUS II). Next, to quantify the detected elements, a reference sample with a known concentration was measured, and then the values ​​of each element were corrected from the X-ray intensity. The power during measurement was set to 3000W, and the content of each element, magnesium, aluminum, silicon, and calcium, was quantified.

[0103] <Measurement of the number of silicon-containing foreign substances and silica foreign substances included in laminates for glass plates>

[0104] Silicon-containing foreign matter contained in the laminate was measured at approximately the center of the laminate using a scanning electron microscope (manufacturer: Nihon Denshi Co., Ltd., model: JSM-6490LA) and an energy-dispersive X-ray analyzer (manufacturer: Oxford Instruments Co., Ltd., model: X-MAXN50). The acceleration voltage during observation was set to 20 kV.

[0105] When measuring silicon-containing foreign matter and silica foreign matter with a longest diameter of 0.5 μm or more and 50 μm or less, first, 100 areas of 0.1 mm × 0.1 mm were measured, and foreign matter other than carbon with a longest diameter of 0.5 μm or more was counted. For each foreign matter detected by this reflection electron detector, the size was calculated from the number of pixels, and for each particle with a longest diameter of 0.5 μm or more and 50 μm or less, the element was analyzed one by one using an energy-dispersive X-ray analyzer, and among the elements excluding carbon and oxygen, the number of particles containing 10 wt% or more of silicon (silicon-containing foreign matter) and particles containing 80 wt% or more of silicon (silica foreign matter) was counted.

[0106] In addition, the same was done when measuring silicon-containing foreign matter and silica foreign matter with the longest diameter being 1㎛ or more and 10㎛ or less.

[0107] Measurement and Evaluation of Foreign Matter Remaining on the Surface of Glass Plates

[0108] From a glass plate bale stored for 10 days, the glass plate closest to the inclined plate of the pallet was removed, and after cleaning the glass plate, the number of foreign substances remaining on the surface of the glass plate was measured using an optical inspection device (Manufacturer: Hitachi High-Tech Fine System Co., Ltd., Model: GI). Cleaning of the glass plate was performed by spraying pure water while conveying the glass plate in a horizontal direction and rubbing it with a PVA sponge.

[0109] Foreign substances present on the surface of the glass plate were designated as A if fewer than 50 were present, B if 50 or more but less than 60 were present, and C if 60 or more were present.

[0110] (Example 1, Example 2)

[0111] As a raw material, virgin pulp with a high calcium content was diluted with groundwater filtered through a process filter with a filtration precision of 200 μm to obtain a raw material solution for lamination. The above raw material solution was expanded to a uniform thickness and dehydrated to obtain a wet sheet. The obtained wet sheet was dehydrated by pressing it with a press roller, and the wet sheet after pressing was dried in an atmosphere of approximately 120°C to obtain a laminate.

[0112] (Example 3, Example 4)

[0113] It was manufactured in the same manner as Example 1, except that virgin pulp with a high silicon content was used as the raw material.

[0114] (Example 5)

[0115] It was manufactured in the same manner as Example 1, except that virgin pulp with a high silicon content and a low calcium content was used as the raw material.

[0116] (Example 6, Example 7)

[0117] It was manufactured in the same manner as Example 1, except that virgin pulp with a high concentration of silicon and magnesium content and talc was added as a raw material.

[0118] <Result>

[0119] Table 1 shows the measurement and evaluation results. According to Table 1, when the silicon concentration was 200 ppm or less and the X / Y ratio (silicon concentration divided by calcium concentration) was 4.00 or less, the contamination level was A or B. On the other hand, when the silicon concentration exceeded 200 ppm and the X / Y ratio was greater than 4.00, the contamination level was C in all cases.

[0120] As a result, it can be understood that silicon concentration and the X / Y ratio are related to the number of silica particles present in the lamination and the contamination of the glass plate.

[0121] Explanation of the symbols

[0122] 10 … glass plate bale 12 … glass plate laminate 14 … glass plate 16 … Lamination for glass plates 18 … inclined plane 22 … anticipation 24 … loading rack 42 … Laminated roll 100 … Manufacturing device for laminated glass plates 112 … Head box 114 … wire part 116 … lower wire 118 … upper wire 120 … Press Part 124 … Dryer part 126 … Calendar Part 128 … reel 130 … Jumbo Roll 134 … cutter 136 … Winder

Claims

Claim 1 A laminate for glass plates containing cellulose pulp, having a basis weight of 10 g / m² or more and 100 g / m² or less, wherein the laminate for glass plates is characterized in that, when silicon concentration measured by fluorescent X-ray analysis is X and calcium concentration is Y, X is 10 ppm or more and 150 ppm or less, Y is 20 ppm or more and 400 ppm or less, and the X / Y ratio, which is the value obtained by dividing the silicon concentration by the calcium concentration, is 4.00 or less. Claim 2 In claim 1, the laminate for glass plates is a laminate for glass plates having an X / Z ratio of 3.00 or less, wherein the silicon concentration is divided by the magnesium concentration when the magnesium concentration measured by fluorescent X-ray analysis is denoted as Z. Claim 3 In paragraph 2, the above Z is a laminate for glass plates having a value of 20 ppm or more and 100 ppm or less. Claim 4 In any one of claims 1 to 3, the laminate for a glass plate is a laminate for a glass plate in which the number of silicon-containing foreign substances of 0.5㎛ or more and 50㎛ or less present on at least one laminate surface is 2000 pieces / mm² or less. Claim 5 In any one of claims 1 to 3, the laminate for a glass plate is a laminate for a glass plate in which the number of silicon-containing foreign substances of 1 μm or more and 10 μm or less present on at least one laminate surface is 1000 pieces / mm² or less. Claim 6 In any one of claims 1 to 3, the laminate for a glass plate is a laminate for a glass plate in which the number of silica foreign substances of 0.5㎛ or more and 50㎛ or less present on at least one laminate surface is 100 pieces / mm² or less. Claim 7 In any one of claims 1 to 3, the laminate for a glass plate is a laminate for a glass plate in which the number of silica foreign substances of 1 μm or more and 10 μm or less present on at least one laminate surface is 50 pieces / mm² or less. Claim 8 In any one of paragraphs 1 to 3, the laminate for glass plates is a laminate for glass plates having a vapor resistance of 5 seconds or more. Claim 9 A glass plate laminate comprising at least two glass plates laminated together, and having a glass plate laminate described in any one of claims 1 to 3 between adjacent glass plates. Claim 10 A glass plate bale comprising a glass plate laminate described in claim 9 and a pallet for loading the glass plate laminate. Claim 11 delete

Citation Information

Patent Citations

  • Wood pulp for glass plate slip sheet and use thereof, slip sheet for glass plate, laminate using the same, protection method of glass plate and inspection method of wood pulp for glass plate slip sheet or slip sheet for glass plate

    JP2017210286A

  • Glass interleaving paper

    KR102054133B1